Manajemen Mutu Layanan Ta’lim Quran lil Aulad (TQA) di Yayasan Team Tadarus “AMM” Yogyakarta - Supriati H. Rahayu; Hilman Haroen; TW Budiutomo; Nginayatul Khasanah; Nuryati Nuryati (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2020)
Qualitative research on the quality of Quran education services has a specificity according to the character of the material that prioritizes recitation and reading recitation, especially for TQA education organized by the Tadarus Team Foundation for the Young Generation Mosque and Musholla (YTT "AMM") Kotagede Yogyakarta. It takes the form of further education after the children study at TPA or TPQ. This requires a specific quality of service in learning for child santri compared to those who are beginners. Academic services are no longer limited to mastering the Iqro book as an important reference for learners at the beginner level at TPA "AMM". However, the learning services cannot be compared to those of advanced Quran learners for more independent adults. The data were analyzed descriptively after being collected through observation, documentation, in-depth interviews with informants who were equipped with triangulation. The quality assurance of Quran learning services at TQA has been carried out consistently in improving the quality of teachers. in services The closeness of ustaz/ah with TQA education students is an advantage that must be cultivated and developed.